42 Performance, Health, and Physiological Responses of Newly-Weaned Cattle Supplemented with Feed Grade Antibiotics or Alternative Feed Additives during Feedlot Receiving. (1st March 2018) - Schubach, K M; Cooke, R; Souza, K A; Schumaher, T F; da Silva, N S; Bohnert, D W; Marques, R
Abstract: This experiment compared performance, health, and physiological responses of cattle supplemented with feed grade antibiotics or alternative feed additives during a 60-d receiving period. Newly-weaned Angus × Hereford calves (63 steers + 42 heifers) originating from 2 cow-calf ranches were obtained from an auction yard on d -2 and road-transported (800 km; 12-h) to a receiving yard. Upon arrival on d -1, shrunk BW was recorded and calves were grouped with free-choice hay, mineral supplement, and water. On d 0, calves were ranked by sex, source, and shrunk BW, and allocated to 1 of 21 pens. Pens were assigned to receive (7 pens/treatment) a free-choice total mixed ration containing: 1) lasalocid (360 mg/calf daily of Bovatec; Zoetis, Florham Park, NJ) + chlortetracycline (350 mg/calf of Aureomycin at cycles of 5-d inclusion and 2-d removal from diet; Zoetis) from d 0 to 31, and monensin only (360 mg/calf daily of Rumensin; Elanco Animal Health, Greenfield, IN) from d 32 to 60 (PC ), 2) sodium saccharin-based sweetener (Sucram at 0.04 g/kg of diet DM; Pancosma SA; Geneva, Switzerland) + blend of natural oils eugenol, cinnamaldehyde, and capsicum (800 mg/calf daily of XTRACT Ruminants 7065; Pancosma SA) from d 0 to 31, and XTRACT only (800 mg/calf daily) from d 32 to 60 (EG ), or 3) no supplemental ingredients (CON ). Feed DMI was recorded from each pen, calves assessed for bovine respiratory disease (BRD ) signs daily, and vaccinated against BRD pathogens on d 0 and 22. Final shrunk BW was recorded on d 61, and blood samples collected on d 0, 6, 11, 22, 32, 43, and 60. Calf ADG was greater ( P = 0.04) in PC vs. EG and tended ( P = 0.09) to be greater in PC vs. CON (1.59, 1.47, and 1.49 kg/d, respectively; SEM = 0.04), whereas G:F tended ( P = 0.09) to be greater in PC vs. CON. Mean serum titers against bovine respiratory syncytial virus were greater in EG vs. PC ( P = 0.04) and CON (tendency; P = 0.08). No further treatment differences were detected ( P ≥ 0.23), including final BW, DMI, BRD incidence (66 ± 4%), plasma concentrations of cortisol, haptoglobin, and IGF-I, and serum titers against other BRD pathogens. Collectively, inclusion of alternative feed additives prevented the decrease in G:F when chlortetracycline and ionophores were removed from a receiving diet, and enhanced calf antibody response to vaccination against bovine respiratory syncytial virus .